Osteogenesis and biofilms formation on titanium surfaces submitted to oxygen plasma immersion ion implantation (Research, Society and Development, 2021)
The objectives of this study were to characterize titanium (Ti) surfaces treated by ion implantation by immersion in oxygen plasma (O-PIII) at different temperatures, correlating these implanted layers with therapeutic effects and with osteogenesis, as well as the formation of monotypic biofilms microbial. The groups were divided into: a) Ti (pre-treatment) b) Ti O-PIII at 400 ° C. c) Ti O-PIII at 500 ° C. d) Ti O-PIII at 600 ° C. The properties and surface characteristics were evaluated according to the roughness, texture, corrosion resistance, formation of new phases and the identification of chemical compounds present. Cellular analyzes investigated cell interaction, viability, total protein content, alkaline phosphatase and quantification of mineralized nodules using MG-63 cells. The formation of monotypic microbial biofilms, including P. aeruginosa, S. aureus, S. mutans and C. albicans were evaluated. The increase in surface roughness, corrosion resistance and oxygen content, leading to the formation of TiO2-rutile with more intense peaks and in greater numbers according to the increase in the substrate temperature, ionic implanted Ti samples was observed. There was also a significant increase in cell viability, total protein production, alkaline phosphatase activity and formation of mineralization nodules for the group treated with O-PIII at 600ºC compared to other groups, in addition to a reduction of microorganisms in the groups treated with O- PIII. Therefore, treatment with O-PIII at 600ºC in Ti grade IV showed favorable results for its use.